2022
DOI: 10.3389/fpsyg.2022.921056
|View full text |Cite
|
Sign up to set email alerts
|

Word complexity modulates the divided-word effect during Chinese reading

Abstract: The present study examined the influence of word complexity on the divided-word effect. By manipulating presentation conditions (line-final presentation vs. divided-word presentation vs. line-initial presentation) and visual complexity (high vs. low), we found a significant divided-word effect that the reading times such as gaze duration and total reading time were significantly longer in the divided-word presentation condition than in both the line-final and line-initial presentation conditions. On the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recall that, in standard Chinese text, the boundaries of line-final words are not respected in relation to line endings, thereby resulting in some situations in which line-final words would have their constituent characters split over two lines. Li et al ( 2012 ) demonstrated that when words are split across lines in Chinese there is significant disruption to lexical identification, reporting that readers experienced more difficulty processing words presented in this way than when words were presented as a whole (see also Zhang et al, 2022 ). In the present study, we maintained the integrity of line-final words such that all line-final words appeared in their integrity on the same line, to minimize any potential processing difficulty inherent in splitting words across different lines of text.…”
Section: Methodsmentioning
confidence: 99%
“…Recall that, in standard Chinese text, the boundaries of line-final words are not respected in relation to line endings, thereby resulting in some situations in which line-final words would have their constituent characters split over two lines. Li et al ( 2012 ) demonstrated that when words are split across lines in Chinese there is significant disruption to lexical identification, reporting that readers experienced more difficulty processing words presented in this way than when words were presented as a whole (see also Zhang et al, 2022 ). In the present study, we maintained the integrity of line-final words such that all line-final words appeared in their integrity on the same line, to minimize any potential processing difficulty inherent in splitting words across different lines of text.…”
Section: Methodsmentioning
confidence: 99%